2018
DOI: 10.30924/mjcmi/2018.23.1.139
|View full text |Cite
|
Sign up to set email alerts
|

Managing group work in the classroom: An international study on perceived benefits and risks based on students’ cultural background and gender

Abstract: Working in groups has become an essential

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 31 publications
(27 reference statements)
2
6
0
1
Order By: Relevance
“…The present study suggested some strategies like regular monitoring, choosing tasks that required the group to work together and asking individuals to submit evidence of their contribution as a possible solution though time is a concern. This is in line with the suggestions made by Šeric & Praničević (2018) and Davis (2009).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The present study suggested some strategies like regular monitoring, choosing tasks that required the group to work together and asking individuals to submit evidence of their contribution as a possible solution though time is a concern. This is in line with the suggestions made by Šeric & Praničević (2018) and Davis (2009).…”
Section: Discussionsupporting
confidence: 93%
“…The lack of collaboration was also due to absence of individual accountability. The study pointed out that there is existence of free riders which was in line with the study conducted by Šeric & Praničević (2018). They mentioned the existence of free riders as the major perceived risk of group work.…”
Section: Discussionsupporting
confidence: 79%
“…Along with this, it was found that the teachers considered their distribution of tasks and mark inequitable and unfair. In support of this, previous works showed assigning a task to the entire group instead of dividing for each group member, resulted in harboring free-riding while sharing of tasks reduced free riding and promoted individual accountability and greater learning gains ( Bailey et al., 2012 ; Chang and Brickman, 2018 ; Šerić and Praničević, 2018 ).…”
Section: Discussionmentioning
confidence: 79%
“…A team leader is someone who guides and monitors team member and team performance to promote task and interpersonal advances (Northouse, 2016). A team member is someone who is working on a team (Šeri & Prani evi , 2018). Lastly, team development is defined as the different stages a team goes through.…”
Section: Definition Of Key Termsmentioning
confidence: 99%